Pyritic metals sequestration on mine dumps treated with oyster mushroom (Pleurotus ostreatus, Jacq.et Fr.) - Masaka, Johnson; Mutambu, Marshall; Mhindu, Rangarirayi; Muringaniza, Kudakwashe (Springer Verlag, 2017)
Background Mining activities can lead to the generation of large quantities of heavy metal laden wastes which are released into the environment in an uncontrolled manner, causing widespread contamination of the ecosystem. Bioremediation is an innovative and promising technology available for removal and recovery of heavy metals from polluted environments.